Pengaruh Keputusan Investasi, Leverage, Profitabilitas, Dan Rasio Aktivitas Terhadap Price Book Value Pada Perusahaan Infrastruktur Yang Terdaftar Di BEI Tahun 2020 - Irma Amilia; Rendra Erdkhadifa (Shafin: Sharia Finance and Accounting Journal, 2022)
This research was motivated by an Infrastructure Company which became the focus that several sectors experienced a decline in stock prices, financial performance and economic growth in Indonesia due to the Covid-19 pandemic outbreak. Therefore, to collect empirical data about the impact of investment decisions, leverage, profitability, and activity ratios on price book value in Infrastructure Companies listed on the IDX in 2020, the researchers raised issues and factors that are expected to have an impact on the book price or value. company (PBV). This study use a quantitatives approach and the type of associatiive research. Because the data is secondary, it is obtained from the annual financial reports of infrastructure companies that will be listed on the IDX in 2020 through the IDX's official website. The sample of this study includes 40 annual financial statement data, and multiple regression analysis is used to analyze the data. Leverage is one of the variables which according to the test results have an effect on Price Book Value, while investment decisions, profitability, and activity ratios have no effect on Price Book Value.